Power quality improvement and reactive power compensationusing enhancedsliding mode controllerbased shunt active power filter and static VAR compensator - Rajesh, T; Rajeswari, S (International Journal of Engineering and Technology, 2018)
The power quality is the challenging criteria in all equipment’s at all levels comprise industrial sectors and consumer places. Some parameters are very sensitive which may affect and disturb the power quality. These parameters are harmonic current, power compensation and voltage sag. Providing the source without these parameters with efficient power quality is essential. Hence by selecting proper device the power output may reach without any interruption along with linear, non-linear and unbalanced loads. This paper introduces a Sliding Mode Controller (SMC), a very effective controller implemented with Shunt active filter and Static VAR Compensator (SVC) FACTS device which increases the reactive power compensation and suppresses the harmonic to enhance the system performance with high reliability.